Routine Lateral Level V Dissection May Not Be Necessary for Papillary Thyroid Microcarcinoma With Lateral Lymph Node Metastasis: A Retrospective Study of 252 Cases - Xue, Shuai; Wang, Peisong; Zhang, Qiang; Yin, Yue; Guo, Liang; Wang, Ming; Jin, Meishan; Chen, Guang (Frontiers in Endocrinology, 2019)
Background: Lateral lymph node metastasis (LLNM) is associated with distant metastasis, locoregional recurrence and cancer-specific mortality, although the prevalence of LLNM among patients with papillary thyroid microcarcinoma (PTMC) is relatively low. The potential benefits and risks of routine lateral level V dissection (LVD) for PTMC with LLNM have not been previously investigated. Methods: A total of 6880 consecutive PTMC patients who underwent initial surgery at the 1st Hospital of Jilin University from January 2009 to July 2017 were retrospectively analyzed. A total of 252 N1b PTMC patients were enrolled in our study. Results: The overall and occult metastasis rates in level V lymph nodes were 21.4% and 6.4%, respectively. Patients with N1b PTMC who received LVD did not show a significantly lower DFS than that of patients who did not receive LVD (hazard ratio=1.11 [CI 0.38–3.21]; p = 0.85). Meanwhile, LVD simultaneously increased the hospital stay and cost (p=0.03; 0.02). Multivariate logistic regression analysis revealed that 3-level simultaneous metastasis in the lateral neck was an independent risk factor for level V metastasis (odds ratio=8.6 [CI 1.42–51.72]; p = 0.02). Conclusions: Because of the low metastasis rate in level V lymph nodes, the lack of benefit for recurrence, the longer hospital stay and the higher cost associated with LVD, N1b PTMC patients without clinical level V metastasis may not need to undergo routine dissection. Prophylactic LVD may be recommended only for patients with N1b PTMC with 3-level simultaneous metastasis.